Fly Ash-Supported Photocatalysts: Synthesis, Applications, and Advances in Modification Technology - Cheng-Gong Lu; Chu-Jie Jiao; Xiu-Cheng Zhang; Wen-Cong Lin; Xue-Fei Chen (Crystals)
Fly ash, a primary solid waste product of coal combustion, poses severe threats to human health and the environment due to its massive accumulation. Leveraging the modified porous structure and engineered adsorptive properties of fly ash, its integration with nano-photocatalytic materials can achieve dispersion and stabilization of the photocatalyst, significantly enhancing photocatalytic activity while enabling a synergistic effect between adsorption and photocatalysis. This paper focuses on the issue of agglomeration in semiconductor photocatalytic materials and briefly reviews the preparation methods and applications of modified fly ash-supported photocatalytic materials from both domestic and international perspectives in recent years. Initially, the properties and modification techniques of fly ash are analyzed, with a special emphasis on three methods for preparing fly ash-based photocatalytic composites: the sol-gel method, hydrothermal synthesis, and liquid-phase precipitation. A comparative analysis of the advantages and disadvantages of these three methods is conducted. Furthermore, the performance of the materials and the positive impacts of fly ash-composite photocatalysts are analyzed in terms of applications such as the degradation of pollutants in water, the degradation of NOx and VOCs gaseous pollutants, self-cleaning properties, and CO2 reduction capabilities. These analyses indicate that fly ash primarily serves as an adsorbent and carrier in these applications. However, as a carrier, fly ash possesses a limited number of active sites, and its modification technology is not yet fully mature. Additionally, research in this area is still in the experimental stage and has not transitioned to engineered production. Therefore, there is a need for continuous improvement in fly ash modification techniques. Furthermore, additional research should be conducted on functional building materials loaded with fly ash-supported photocatalytic materials to enhance their practicality.